2011
DOI: 10.1111/j.1750-3841.2010.02022.x
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Antimicrobial and Spasmolytic Properties of Poliomintha longiflora and Lippia graveolens Essential Oils**

Abstract: The analytical methods using GC-MS and HPLC techniques will be useful for establishing quality control as well as preclinical pharmacological and toxicological parameters of the crude drug P. longiflora, which is widely used as substitute of L. graveolens for medicinal and flavorings purposes. This overall information will be also useful for elaborating scientific and pharmacopoeic monographs of this very Mexican medicinal plant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 32 publications
2
28
0
2
Order By: Relevance
“…Hieron. (Lima et al, 2011), 1,8-cineole at 40% in L. multiflora (Avlessi et al, 2005), and 17% in L. graveolens (Rivero-Cruz et al, 2011). Recently, Cruz et al (2014) reported that the concentration of major constituent from Lippia gracilis Schauer showed little variation between seasons, demonstrating the stability of the chemical composition of the essential oils even with different climatic conditions, confirming the findings of this work and indicating that this behavior could possibly be a characteristic of the species Lippia.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Hieron. (Lima et al, 2011), 1,8-cineole at 40% in L. multiflora (Avlessi et al, 2005), and 17% in L. graveolens (Rivero-Cruz et al, 2011). Recently, Cruz et al (2014) reported that the concentration of major constituent from Lippia gracilis Schauer showed little variation between seasons, demonstrating the stability of the chemical composition of the essential oils even with different climatic conditions, confirming the findings of this work and indicating that this behavior could possibly be a characteristic of the species Lippia.…”
Section: Discussionsupporting
confidence: 76%
“…The essential oils obtained from Lippia species have demonstrated effective relaxation in different smooth muscles, as L. alba in rat mesenteric artery (Maynard et al, 2011) and L. graveolens in guinea-pig ileum (Rivero-Cruz et al, 2011). Thus, aiming to identify L. thymoides as a source of natural product of pharmacological interest, essential oils were tested in different isolated organs.…”
Section: Discussionmentioning
confidence: 99%
“…Several species falling under the common name oregano are found in the genera Origanum and Thymus, native to Europe, and Lippia and Poliomintha, originating from the arid Central and North America. The most popular forms under the common name Mexican oregano are Lippia berlandieri Schauer and Poliomintha longiflora Gray (Rivero-Cruz et al, 2011). Lippia berlandieri Schauer is a common shrub found in arid regions of northern Central America, Mexico, and the southwestern United States, while Poliomintha longiflora Gray is a spindly shrub restricted to arid north-central Mexico, as well as in Haiti.…”
Section: Introductionmentioning
confidence: 99%
“…This plant is used as a food seasoning, as well as against respiratory and digestive diseases (Rivero-Cruz et al, 2011). Mexican oregano oil is characterized by a strong odor and its various biological activities, attributed to the high content of phenolic components carvacrol and thymol (Arcila-Lozano et al, 2004;Avila-Sosa et al, 2010).…”
Section: Introductionmentioning
confidence: 99%